Integrated community case management and community-based health planning and services: a cross sectional study on the effectiveness of the national implementation for the treatment of malaria, diarrhoea and pneumonia. (December 2016) - Ferrer, Blanca; Webster, Jayne; Bruce, Jane; Narh- Bana, Solomon; Narh, Clement; Allotey, Naa-KorKor; Glover, Roland; Bart-Plange, Constance; Sagoe-Moses, Isabella; Malm, Keziah; Gyapong, Margaret
Abstract Background Ghana has developed two main community-based strategies that aim to increase access to quality treatment for malaria, diarrhoea and pneumonia: the Home-based Care (HBC) and the Community-based Health Planning and Services (CHPS). The objective was to assess the effectiveness of HBC and CHPS on utilization, appropriate treatment given and users' satisfaction for the treatment of malaria, diarrhoea and pneumonia. Methods A household survey was conducted 2 and 8 years after implementation of HBC in the Volta and Northern Regions of Ghana, respectively. The study population was carers of children under-five who had fever, diarrhoea and/or cough in the last 2 weeks prior to the interview. HBC and CHPS utilization were assessed based on treatment-seeking behaviour when the child was sick. Appropriate treatment was based on adherence to national guidelines and satisfaction was based on the perceptions of the carers after the treatment-seeking visit. Results HBC utilization was 17.3 and 1.0 % in the Volta and Northern Regions respectively, while CHPS utilization in the same regions was 11.8 and 31.3 %, with large variation among districts. Regarding appropriate treatment of uncomplicated malaria, 36.7 % (n = 17) and 19.4 % (n = 1) of malaria cases were treated with ACT under the HBC in the Volta and Northern Regions respectively, and 14.7 % (n = 7) and 7.4 % (n = 26) under the CHPS in the Volta and Northern Regions. Regarding diarrhoea, 7.6 % (n = 4) of the children diagnosed with diarrhoea received oral rehydration salts (ORS) or were referred under the HBC in the Volta Region and 22.1 % (n = 6) and 5.6 % (n = 8) under the CHPS in the Volta and Northern Regions. Regarding suspected pneumonia, CHPS in the Northern Region gave the most appropriate treatment with 33.0 % (n = 4) of suspected cases receiving amoxicillin. Users of CHPS in the Volta Region were the most satisfied (97.7 % were satisfied or very satisfied) when compared with those of the HBC and of the Northern Region. Conclusions HBC showed greater utilization by children under-five years of age in the Volta Region while CHPS was more utilized in the Northern Region. Utilization of HBC contributed to prompt treatment of fever in the Volta Region. Appropriate treatment for the three diseases was low in the HBC and CHPS, in both regions. Users were generally satisfied with the CHPS and HBC services.